Gel Kombinasi Ekstrak Daun Sirsak dan Daun Jambu Biji Sebagai Obat Anti Jerawat - Yulianti, Rika; Abdassah, Marline; Abdulah, Rizky; Surachman, Emma (Jurnal Farmasi Indonesia, 2015)
This study aims to determine the formulation and testing of anti-acne combination gel activity of ethanol extract of leaves of soursop (Annona muricata L.) and leaves of guava (Psidium guajava L ) in in - vitro and in - vivo. Soursop leaf is traditionally used to treat acne . It is known that asetogenin soursop leaves contains compounds acetogenin, tannins, phytosterols, calcium oxalate, murisin alkaloids, ô°la- vonoids and steroid. Research on anti- acne activity of guava leaf extract has been carried out by Qaâ??dan et al in 2005. Samples were obtained from a combination of extracts of leaves of soursop (Annona muricata L.) and leaves of guava (Psidium guajava L ) using the method of maceration with 96 % ethanol. The preparation is formulated in the form of a gel and tested the minimum inhibitory concentration and antibacterial activity against Propionibacterium acne using Cindala Â® gel for comparison. In-vivo studies conducted using rats (Rattus novergicus) galus Wistar as test animals by administration of Propionibacterium acne bacteria colonies suspense as inducers.The results showed that the combination gel of soursop leaf extract and guava leaf extract has anti bacterial activity against Propionibacterium acne with carbomer gel formulation using as a base. In vivo testing results show that the gel has anti acne activity and statistically signiô°icantly different to the negative control.